Characterization of the complete mitochondrial genome of the Lesser Spotted Woodpecker (Dryobates minor) and its phylogenetic position. Issue 8 (3rd August 2022) - Chen, Junda; Meng, Dehuai; Si, Yuhui; Yu, Meichen; Teng, Liwei; Liu, Zhensheng; Zhou, Xiaoyu
Abstract: In this study, we sequenced and assembled the complete mitochondrial genome of Dryobates minor by next-generation sequencing. The mitochondrial genome of Dryobates minor is 16, 847 bp in length and consists of 13 protein-coding genes (PCGS), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes and 1 control region (CR). The CG content of the mitochondrial genome is 47.46%. Only one overlap among the 13 protein-coding genes was found: ND4L/ND4. Phylogenetic analysis based on a combined mitochondrial gene dataset indicated that the mitochondrial genome of Dryobates minor exhibited a close relationship with that of Picoides pubescens .